2016
DOI: 10.1002/btpr.2320
|View full text |Cite
|
Sign up to set email alerts
|

3D‐liquid chromatography as a complex mixture characterization tool for knowledge‐based downstream process development

Abstract: Knowledge-based development of chromatographic separation processes requires efficient techniques to determine the physicochemical properties of the product and the impurities to be removed. These characterization techniques are usually divided into approaches that determine molecular properties, such as charge, hydrophobicity and size, or molecular interactions with auxiliary materials, commonly in the form of adsorption isotherms. In this study we demonstrate the application of a three-dimensional liquid chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
(42 reference statements)
0
9
0
Order By: Relevance
“…The column dead volume is very important in miniature columns such as the RoboColumns, since the ratio of column volume ( Vnormalcnormalonormall) to column dead volume is smaller. In previous studies, it was found to be 30 μL . The bed porosity ɛnormalb generally lies in between 0.3 and 0.4 for packed chromatography columns.…”
Section: Methodsmentioning
confidence: 86%
See 4 more Smart Citations
“…The column dead volume is very important in miniature columns such as the RoboColumns, since the ratio of column volume ( Vnormalcnormalonormall) to column dead volume is smaller. In previous studies, it was found to be 30 μL . The bed porosity ɛnormalb generally lies in between 0.3 and 0.4 for packed chromatography columns.…”
Section: Methodsmentioning
confidence: 86%
“…Each fraction of interest was analyzed with isocratic experiments at different salt concentrations on RoboColumns containing the respective resin (1, 2 and 3 on POROS 50HS; 4 and 5 on Capto MMC). Fractions collected here were further analyzed with size exclusion measurements, to increase resolution and sensitivity, and UV measurements, to determine the well volume. Typical results of these experiments are shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations